Revision of the punctatus species-group of Dissomphalus Ashmead (Hymenoptera, Bethylidae) - Brito, Chirlei D. De; Azevedo, Celso O. (Zootaxa, 2024)
The Neotropical region is known for its high species diversity. Dissomphalus Ashmead exemplifies this phenomenon, being the most speciose genus within Bethylidae, with 34 species-groups and 287 species. Among these groups, punctatus is one of the smallest, comprising only seven species. The objective of this contribution is to conduct a taxonomic study of punctatus species-group in the Neotropical region. Our results are surprising by discovering forty-six species, thirty-nine of which are new to science: D. alexandrinae sp. nov., D. alzirae sp. nov., D. ameliae sp. nov., D. annae sp. nov., D. antonietae sp. nov., D. ashauerae sp. nov., D. beatrizae sp. nov., D. boriae sp. nov., D. carmenae sp. nov., D. carolinae sp. nov., D. dandarae sp. nov., D. deaneae sp. nov., D. elisae sp. nov., D. elzae sp. nov., D. enedinae sp. nov., D. eulaliae sp. nov., D. evaristoae sp. nov., D. grazielae sp. nov., D. guidonae sp. nov., D. jaquelineae sp. nov., D. johannae sp. nov., D. leliae sp. nov., D. limae sp. nov., D. lispectorae sp. nov., D. luisae sp. nov., D. lumae sp. nov., D. lutzae sp. nov., D. margarethae sp. nov., D. martae sp. nov., D. maryae sp. nov., D. meirelesae sp. nov., D. mirandae sp. nov., D. nisiae sp. nov., D. penhae sp. nov., D. ritae sp. nov., D. silveirae sp. nov., D. soniae sp. nov., D. sueliae sp. nov., D. vivianeae sp. nov. which are described and illustrated. The status of Dissomphalus montanus (Kieffer, 1910), stat. resurr. is resurrected from the synonymy of D. punctatus (Kieffer, 1910) seven are previously described: D. acutipupu Colombo & Azevedo, D. bahiensis Redighieri & Azevedo, D. cuca Colombo & Azevedo, D. montanus (Kieffer), D. napo Evans, D. punctatus (Kieffer) and D. tupinikim Colombo & Azevedo. A key to males of all species in this group is provided. Throughout this paper, we demonstrate the diversity found in the genitalia structures of this group and emphasize their importance in the taxonomy of Dissomphalus.